Kapasitas Dinas Sosial Dalam Penanggulangan Bencana Erupsi Gunung Sinabung Melalui Pendistribusian Jaminan Hidup Dan Isian Hunian Tetap Masyarakat Desa Berastepu - Septiana Br Sembiring; Rudi Kristian P. M (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
This study aims to find out and describe how the capacity of the Social Service in overcoming the eruption of Mount Sinabung through the distribution of life insurance and the filling of permanent housing for the people of Berastepu village. The method used is a descriptive method with a qualitative approach through data collection such as interviews, observations, documentation, and literature studies. The results of research in the field, researchers found that the capacity of the Social Service in disaster management of the Mount Sinabung eruption through the distribution of life insurance and the filling of permanent housing for the berastepu village community has not been maximized. The Social Service Office has distributed assistance to the people of Berastepu Village, but there are still problems seen from human resource indicators that have not been maximized where the employee's educational background is not in accordance with the placement of positions, then facilities and infrastructure, especially work rooms that have not provided comfort for employees, and organizational management indicators, especially information collection, have not been maximized where there is a lag in some community data so that resulting in late distribution of aid.